Quimioterapia neoadjuvante com vimblastina e lomustina no tratamento de um caso de mastocitoma cutâneo canino com múltiplos fatores prognósticos negativos e sobrevida superior a dois anos - Jark, Paulo César [UNESP] (2013)
The clinical and biological behavior of canine cutaneous mast cell tumors is highly variable, making the establishment of prognosis and choose of the best treatment to be instituted a challenge to veterinary oncologists. While there are many chemotherapeutic protocols outlined for treatment of canine cutaneous mast cell tumors, they were evaluated by comparing heterogeneous groups, with different clinical and histopathological prognostic factors, thus making it difficult to select the best protocol to use. The intention of this report is describe the effects of a neoadjuvant protocol with vinblastine and lomustine in a case of grade III / high degree mast cell tumour in perineum, with worse prognosis, based on unfavorable clinical factors (location, tumor size, growth rate ), histopathological characteristics (degree of Patnaik and Kiupel) and immunohistochemistry (immunostaining of Ki-67, kit and P-glycoprotein ) who responded favorably to treatment and has to date a survival of 110 weeks without signs of recurrence disease.